Workforce Analysis of the Procurement Office at Visayas State University- Isabel - Carillo, Izzy Cherub; Diano, Simon Peter (Journal of Interdisciplinary Perspectives, 2025)
The Procurement Office at Visayas State University-Isabel Campus faces significant operational challenges due to insufficient staffing, which has resulted in inefficiencies, increased workload, and various work-related issues. This study aims to determine the optimal staffing level required to address these challenges and improve productivity. The researcher conducted a comprehensive work sampling study over 14 days to observe 1,348 instances of four staff members. The results showed that productivity exceeded the 70-75% standard range because Staff A reached 90.21%, Staff B reached 90.50%, Staff C reached 90.81%, and Staff D reached 93.77%. The research data demonstrates that additional personnel must be hired to prevent burnout and reduce stress while maintaining sustainable performance. The workforce score of 5.052 showed that the current staffing level exceeds the ideal threshold, and the office demands exceed the current team’s capacity. Furthermore, the workload analysis demonstrated that a team of five staff members would maintain an average workload of 90.60%, staying well under the maximum limit of 100%. The study recommends hiring one more staff member to increase the total staff to five for better workload management and operational efficiency. The necessary staffing change will enhance productivity while creating a healthier workplace environment and guaranteeing sustained resource management for similar administrative operations.